2015
DOI: 10.1115/1.4028767
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Sweep Stacking on the Performance of an Axial Fan

Abstract: In modern turbomachinery blade design, nonradial stacking of the profiles is often assumed to be one of the ways to improve the performance of a machine. Instead of stacking the profiles radially, the stacking line is changed by several modifications such as sweep, dihedral, lean, or a combination of these. Nonradial stacking influences secondary flows that have effects on the aerodynamic parameters such as efficiency, pressure rise, blade loading, and stall margin. However, many of the studies in literature a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The second is due to inevitable errors in both the numerical simulation and the experimental test. The deviation between the calculated and experimental data is lower than 5%, which is acceptable according to previous studies [18][19][20][21]. The total grid quantity selected eventually reaches approximately 11.02 × 10 6 .…”
Section: Grid Independencesupporting
confidence: 82%
“…The second is due to inevitable errors in both the numerical simulation and the experimental test. The deviation between the calculated and experimental data is lower than 5%, which is acceptable according to previous studies [18][19][20][21]. The total grid quantity selected eventually reaches approximately 11.02 × 10 6 .…”
Section: Grid Independencesupporting
confidence: 82%
“…Gümmer et al (2000) studied sweep and dihedral effects in axial compressor stators and demonstrated that positive sweep and positive dihedral could reduce end wall losses and increase operating range on compressors. Ilikan et al (2015) found that forward sweep and backward sweep do not significantly affect aerodynamic performance of a fan at the design flow rate in spite of the occurring modifications of the local blade pressure distribution. However, at low flow rate, forward sweep and backward sweep have positive and negative effects on the fan performance, respectively.…”
Section: Introductionmentioning
confidence: 93%
“…Other geometrical considerations such as low hub-to-tip ratios have been accurately predicted using careful turbulence modeling, boundary conditions, trailing edge shape, and areas of non-aerodynamic shape sections at low rotational speeds. 20 Nazmi Ilikan and Ayder, 21 CFD is used as a tool to determine the effects of backward sweep and forward sweep angles in blade design; moreover, it was determined that forward sweep performed better at low rotational speeds but backward sweep fans' performance deteriorated.…”
Section: Introductionmentioning
confidence: 99%